ADHERENCE TO INHALER THERAPY IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE AND CONTRIBUTING FACTORS - Özdemir , Sevda Tűzűn; Yeşilbalkan , Öznur Usta; Akyol , Asiye (PROFESSIONAL STUDIES: Theory And Practice, 2024)
Chronic Obstructive Pulmonary Disease (COPD) is a leading cause of morbidity and mortality worldwide, with inhaler therapy being a cornerstone of its management. This review aims to evaluate adherence to inhaler therapy among COPD patients and identify factors influencing this adherence. A comprehensive literature search was conducted using databases such as PubMed, Scopus, and Web of Science, focusing on studies published between 2010 and 2023. The findings indicate that adherence rates to inhaler therapy range between 20% and 60%, primarily due to factors such as patient education, inhaler technique, and comorbid conditions. The review highlights the importance of effective patient education and simplified inhalation devices to improve adherence and, consequently, health outcomes in COPD patients.